Solution Atomic Layer Deposition of Smooth, Continuous, Crystalline Metal-Organic Framework Thin Films - Barr, Maissa; Nadiri, Soheila; Chen, Dong Hui; Weidler, Peter G.; Bochmann, Sebastian; Baumgart, Helmut; Bachmann, Julien; Redel, Engelbert (Chemistry of Materials, 2022)
For the first time, a procedure has been established for the growth of surface-anchored metal-organic framework (SURMOF) copper(II) benzene-1,4-dicarboxylate (Cu-BDC) thin films of thickness control with single molecule accuracy. For this, we exploit the novel method solution atomic layer deposition (sALD). The sALD growth rate has been determined at 4.5 Å per cycle. The compact and dense SURMOF films grown at room temperature by sALD possess a vastly superior film thickness uniformity than those deposited by conventional solution-based techniques, such as dipping and spraying while featuring clear crystallinity from 100 nm thickness. The highly controlled layer-by-layer growth mechanism of sALD proves crucial to prevent unwanted side reactions such as Ostwald ripening or detrimental island growth, ensuring continuous Cu-BDC film coverage. This successful demonstration of sALD-grown compact continuous Cu-BDC SURMOF films is a paradigm change and provides a key advancement enabling a multitude of applications that require continuous and ultrathin coatings while maintaining tight film thickness specifications, which were previously unattainable with conventional solution-based growth methods.
CRIS-Team Scopus Importer:2022-11-25